Perancangan Dan Implementasi Aplikasi Pencarian Lokasi Bank Bjb (bank Dan Atm) Di Kota Bandung Disertai Rute Terpendek Pada Platform Android - Hamdan Ramdhani; R. Rumani M; Randy Erfa S (eProceedings of Engineering, 2015)
Bank BJB (West Java, Banten) is a Regional Enterprise which are being developed in the area of West Java. BJB Bank customers not only domiciled or residing in Bandung, even outside the city. So, customers require navigation or guidance to find close distence for location of BJB Bank and ATM, in order to facilitate the transaction for them. In this final project, created a mobile app-based GPS (Global Positioning System) on the Android platform. Android is used for current users of the Android platform. Because Android platform has developed very rapidly. So that this application is expected to help for users of Android (especially customers) to find the location of BJB Bank and ATM in Bandung that they are looking for. From some of the results of tests performed, the alpha testing showed that these applications can run all its functions and as expected. While in beta testing conducted through questionnaires showed that these applications help people to finding the location of BJB Bank and ATM in the city of Bandung with the shortest route. Keywords : Bank BJB (Bank Jawa Barat), BJB Bank customers, Customers, Mobile app, Android platform, Android, GPS (Global Positioning System), Alpha, Beta.